Prediction and Impact of Supersaturated Total Dissolved Gas in Flood Discharge of Flood Control Reservoirs in Southwest Mountain Areas: A Case Study in Jiangjiakou Reservoir - ZHANG Zhihao; ZHANG Peng; LIANG Ruifeng; WANG Qingfeng; WANG Yuanming; LI Kefeng (Renmin Zhujiang)
The supersaturated total dissolved gas (TDG) can be generated by high dam flood discharge, which will cause the downstream fish to get gas bubble disease and even die. However, the impact of supersaturated TDG on fish during flood discharge in flood control reservoirs in mountainous areas of Southwest China remains unclear. It is of great research significance and theoretical value to study the formation law of supersaturated TDG during flood discharge of flood control reservoir and its influence on fish resources in the downstream water. This paper develops an impact assessment framework of supersaturated TDG during high dam flood discharge by coupling the longitudinal one-dimensional hydrodynamic model, the supersaturated TDG generation model, the hybrid model, and the longitudinal one-dimensional supersaturated TDG transportation and dissipation model. The framework is applied in Jiangjiakou Reservoir in southwest mountain areas, which is a typical high dam, to explore the TDG generation levels and the characteristics of supersaturated TDG transportation and dissipation under the dam under four typical flood discharge scenarios. The four scenarios are using the surface spillway to discharge the flood once in two years, using the surface spillway to discharge the flood once every five years, using the bottom outlet discharge cavity to discharge the flood once every two years, and using the bottom outlet discharge cavity to discharge the flood once every five years. Based on the results, this paper analyzes the impact of supersaturated TDG on the key protected fish downstream of the dam. The results show that the TDG saturations of the four scenarios are 110.9 %, 115.4 %, 113.7 %, and 119.9 % respectively. With the transportation and dissipation of TDG under the dam, the TDG concentration of each river section under each condition is lower than 115%, except the river reach between Jiangjiakou dam site and river section downstream of the dam with a distance of 2.7 km (the surface spillway to discharge the flood once in five years) and the river reach between dam site and Tongjiang river confluence (the bottom outlet discharge cavity to discharge the flood once every five years); ② In all four flood discharge scenarios, supersaturated TDG will not have adverse effects on the silver carp; and ③ the hydrodynamics shows that the water depths of the river reaches downstream of dam meet the compensation water depth for Rock carp under all scenarios, and this species will not be affected by supersaturated TDG after using the compensation water depth. The research results provide technical support for the assessment of the impact of high dam flood discharge on the water ecology under the dam, which can help reservoir managers make mitigation measures for fixed-point restoration.